Circadian synchronization differentially modifies cytokine-mediated transcriptomic remodeling and cell death in INS-1 cells and mouse islets - Phillip Alexander Keller Andersen; Rasmus H. Reeh; Isabel Sanders; Emilie Bender Overlund; Georgia Katsioudi; Cecilia Jiménez-Sánchez; Emil Zeng Skovhøj; Anniek Frederike Lubberding; Charna Dibner; Thomas Mandrup-Poulsen (iScience)
Summary: Perturbation of the β-cell circadian clock causes oxidative stress and secretory failure, and proinflammatory cytokines disrupt the β-cell core clock. We hypothesized that cytokine-mediated clock perturbation in β-cells depends on circadian synchronization status. Cytokine-mediated core clock mRNA expression in non-synchronized insulin-producing INS-1 cells were potentiated upon synchronization, which were differentially translated into alterations in protein levels. Synchronization sensitized INS-1 cells to cytokine-mediated cytotoxicity, associated with potentiation of NF-κB activity. Inhibition of NF-κB abrogated cytokine-mediated clock gene-expression independent of synchronization status and reversed cytokine-mediated period lengthening. In contrast, in murine islets, cytokines generally reduced core clock mRNA expression independently of synchronization status or NF-κB activity. Synchronization prevented cytokine-mediated cytotoxicity, but not NF-κB activity to a degree comparable to that of KINK-1, while alterations in islet rhythmicity were unaffected by NF-κB inhibition. In conclusion, circadian synchronization differentially modifies cytokine-mediated transcriptomic remodeling and cell death in INS-1 cells and murine islets, depending on NF-κB involvement.